Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3389/fpsyg.2012.00365
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Threat Appraisal and Depression after First Myocardial Infarction

Abstract: The present study investigated cardiac threat appraisal and its association with depression after first myocardial infarction (MI). A semi-structured interview allowing for DSM-IV-axis I diagnoses was administered to 36 patients after first MI. Patients completed self-reports 5–15 days after the MI (time 1), 6–8 weeks later (time 2), and again 6 months later (time 3). Assessments at time 1 included indices of cardiac threat appraisal, locus of control, coping, and depression while at time 2 and time 3 only mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Recent studies did find support for the relevance of rumination both for self-reported cardiac symptoms such as fatigue or sleep problems (León et al, 2010) and for depressive symptoms (e.g., Garnefski and Kraaji, 2010), although not consistently. However, Vögele et al (2012) did not observe any associations of rumination with future depression (self-reported and clinically diagnosed according DSM-IV) in patients after an MI. However, Vögele et al (2012) did not observe any associations of rumination with future depression (self-reported and clinically diagnosed according DSM-IV) in patients after an MI.…”
Section: Ruminationcontrasting
confidence: 65%
See 3 more Smart Citations
“…Recent studies did find support for the relevance of rumination both for self-reported cardiac symptoms such as fatigue or sleep problems (León et al, 2010) and for depressive symptoms (e.g., Garnefski and Kraaji, 2010), although not consistently. However, Vögele et al (2012) did not observe any associations of rumination with future depression (self-reported and clinically diagnosed according DSM-IV) in patients after an MI. However, Vögele et al (2012) did not observe any associations of rumination with future depression (self-reported and clinically diagnosed according DSM-IV) in patients after an MI.…”
Section: Ruminationcontrasting
confidence: 65%
“…This might be particularly relevant for those patients who perceive their health condition as controllable (Park et al, 2012). Interestingly, patients who perceived higher threat reported to make less use of these strategies (Vögele et al, 2012). In the study by Vögele et al (2012), the coping strategies 'threat minimization' and 'search for affiliation' were associated with lower depression scores immediately after the MI and up to 6 months later (Vögele et al, 2012).…”
Section: Approach Versus Avoidance Coping Strategiesmentioning
confidence: 83%
See 2 more Smart Citations
“…In a longitudinal study on cardiac patients, for example, 'threat minimization' and 'search for affiliation' assessed only days after a MI both predicted lower depression scores 2 and 6 months after the MI, respectively, suggesting an important prognostic role for cognitive appraisal processes in the early period after a cardiac event (Vögele et al, 2012). In a longitudinal study on cardiac patients, for example, 'threat minimization' and 'search for affiliation' assessed only days after a MI both predicted lower depression scores 2 and 6 months after the MI, respectively, suggesting an important prognostic role for cognitive appraisal processes in the early period after a cardiac event (Vögele et al, 2012).…”
Section: Cognitive Stylesmentioning
confidence: 99%